KISHVA CONFIDENT OF SHAPING CYC TO FACE GLOBAL CHALLENGES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 1 December 2015 " I am truly grateful to Universiti Sains Malaysia (USM) and those who have assisted me in shaping me into who I am today," those were the words in the email of the newlyelected Chairperson of the Commonwealth Young Council (CYC) Kishva Ambigapathy, sent from Malta, the venue of the 24th Commonwealth Heads of Government Meeting (CHOGM).